Zinc concentrations in the cerebrospinal fluid of normal adults and patients with neurological diseases. Issue 8 (August 1982) - Palm, R; Hallmans, G
Abstract : Zinc concentrations in CSF were determined with flame atomic absorption spectrophotometry in patients assumed to have a normal CSF. No sex difference was found. There was a correlation between zinc, protein and albumin concentrations in CSF. In patients with increased protein levels in CSF or subarachnoid haemorrhage increased zinc concentrations were found.